2020
DOI: 10.3389/fpsyg.2020.00211
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Use Disorder and Associations With Depression and Anxiety Symptoms: A Systematic Review of Recent Research in China

Abstract: Background: An increasing number of studies have investigated Social Networks Use Disorder (SNUD) among Western samples. In this context, the investigation of SNUD in Asia and especially in China has been much neglected. This poses a gap in the literature; it has been estimated that more than one billion Chinese people are using Chinese social networking sites (SNSs). Of note, many of these Chinese SNSs are rather unknown to researchers in Western countries. Aims: The primary objective of the present systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 99 publications
2
23
0
3
Order By: Relevance
“…A new large-scale study by Marengo et al ( 2020 ) recently observed that social media users differ from non-users, with users (of Facebook-owned platforms) being younger, more often female and slightly more extraverted than non-users. Works such as by Brailovskaia and Margraf ( 2017 ) and Sindermann et al ( 2020a , b ), yielded insights that certain personality traits, such as being more neurotic/narcissistic, are associated with higher tendencies toward problematic social media use or social networks use disorder , with the terminology itself being a matter of fierce debate among scientists (Hussain et al, 2020 ; Wegmann et al, 2020 ; Montag et al, in press ).…”
Section: Much Research Investigating Detrimental Aspects Of Social Media Use Focuses On Person Characteristics and Happens In Isolation Fmentioning
confidence: 99%
“…A new large-scale study by Marengo et al ( 2020 ) recently observed that social media users differ from non-users, with users (of Facebook-owned platforms) being younger, more often female and slightly more extraverted than non-users. Works such as by Brailovskaia and Margraf ( 2017 ) and Sindermann et al ( 2020a , b ), yielded insights that certain personality traits, such as being more neurotic/narcissistic, are associated with higher tendencies toward problematic social media use or social networks use disorder , with the terminology itself being a matter of fierce debate among scientists (Hussain et al, 2020 ; Wegmann et al, 2020 ; Montag et al, in press ).…”
Section: Much Research Investigating Detrimental Aspects Of Social Media Use Focuses On Person Characteristics and Happens In Isolation Fmentioning
confidence: 99%
“…nonetheless, it also reinforces problematic use and aggravates the avoidance of off-line interactions. 41 Furthermore, studies have found that people with higher social phobia interacted more with others online rather than off-line, suggesting that the internet promotes online friendships at the expense of face-to-face ones. 42,43…”
Section: Social Phobia and Psmumentioning
confidence: 99%
“…Current studies mainly focused on the popular social media in Western countries such as Facebook and Twitter. Different from the most popular social media platforms in Western countries, Weibo, WeChat, QQ, and Qzone are the most popular social media platforms for communication and information seeking in China (Hussain et al, 2020 ). Despite the increase in social media research in recent years, few studies have focused on Weibo, WeChat, and QQ.…”
Section: Introductionmentioning
confidence: 99%